Hubungan tingkat pengetahuan dengan sikap perawat Tentang perawatan luka diabetes menggunakan Teknik moist wound healing - Maria - Septiyanti; Siti Rahmalia HD; Arneliwati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this study was to identify relationship between the level of nurse’s knowledge with the result of attitudes diabetic wounds dressing by moist wound healling technique. The design of study was description of correlation with cross-sectional method. The study conducted in the medical surgical wards of Eka Hospital Pekanbaru, with total number of 54 respondents. The sampling method was simple random sampling. The research used questionnaires to collect data, the knowledge had validity 0,469-0,911 > 0,444 and reliability was 0,951. The validity of attitude questionare was 0,462-0,809 > 0,444 and reliability was 0,873. The data was analized by univariate and bivariate . The result of univariate showed that there was mayority of respondent had high level of knowledge about diabetic wounds dressing by moist wound healling technique (59,3%) and has mayority high positive attitude (53,7%). According to result of bivariate there was more significan between the level nurses’s knowledge with attitude in diabetic wounds dressing by moist wound healling technique (p value: 0,033). Based on the result of study, the study suggest that the Eka Hospital Pekanbaru hospital should make the standar procedures to be used as consideration for immediately for wound care diabetes with moist wound healing technique. Keywords: attitudes, knowledge, techniques moist wound healing